Plants sold in traditional marketplace in West Java highland: an ethnobotanical analysis - Fitriah, Lia; Mulyanto, Dede (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2025)
Traditional markets are crucial for sustaining plant diversity, local food systems, and cultural heritage. They also function as learning spaces for the diversity and cultural connections of food plants. This study documents the diversity and utilization of plant species traded in a traditional marketplace in West Java’s highland, Indonesia. Data were collected through stall surveys, observations, and semi-structured interviews with 38 traders. A total of 96 species from 31 families were recorded. Fabaceae and Solanaceae were the most represented families (11 species each). Vegetables were the largest category of use (47%); fruits (53%) and leaves (25%) were the most frequently used parts. Most (83%) of the plants sold were exotic, with only 21% being native species. Eight edible wild plant species, including Centella asiatica and Solanum nigrum, remain an essential part of the traditional diet. Women dominate the vegetable trade (64.51%); most vendors reported having 5–20 years of experience. These findings highlight that traditional markets play a crucial role in preserving and serving as learning spaces for plant diversity, local food systems, and cultural heritage.